Regardez-moi, je vous regarde ; Auto Film - Beskardes, Levent, 1949- (1996)
De dove filmmaker en kunstenaar Levent Beskardes laat zien hoe hij zijn films maakt. Hij doet alles alleen.
Regardez-moi, je vous regarde is a black-and-white film from 1996 with sound, in French Sign Language with English subtitles, about Kōji Inoue, a Deaf Japanese photographer. Auto-film is a series of silent, color films made in 2003, in French sign language with French subtitles. The first sequence depicts Beskardes' drawings representing the Seven Deadly Sins. The second section, Essais, is an artistic film in which the camera follows the director around his apartment. The last piece, Répétition d'un poème, shows Beskardes and Fanny Corderoy du Tiers signing a poem in a very dramatic manner